The effects of browning related water chemistry variables (DOC, iron and pH) on macroinvertebrate communities across streams - Olsson,Gustav (2023)
Browning - increased water colour of freshwater, caused by rising dissolved organic matter and iron concentrations - has been widely reported and studied during the past 30 years. Browning has affected a wide range of organisms in aquatic ecosystems, however little attention has been given to macroinvertebrates in streams and especially regarding iron concentration. In this study, I include the effects of organic matter, iron and pH on invertebrates collected from 20 sites within a stream catchment in Southern Sweden, with an aim to separate effects of the water chemistry variables on the invertebrate community. High iron concentrations and low pH negatively affected the invertebrate abundance, biomass and species richness while DOC lacked significant impact on the invertebrate community. However, DOC could have indirectly affected the invertebrates due its influence on pH. Effects of iron concentration on invertebrates may be direct since the effect could be separated from other water chemistry variables. The negative impacts of water chemistry variables linked to browning could be connected to land-use due to forestry practices.